Mary had a little glam - Sauer, Tammi (Sterling Children's Books, 2016)
"Mary had a little glam that grew into a lot. And everywhere that Mary went, she wasn't hard to spot. But on the day she started school, she caught some by surprise. Sweet Mary shrugged and hugged her mom. "I must accessorize."'--Page 4 of cover.